Total quality management in classroom at university level in Islamabad City - Tanvir Kayani (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
The progress of a country inter-depends on the quality of education provided to its citizens. Higher level Education is the most important stage in education system of any country. This stage provides educated graduates and skilled workers that immediately enters into the practical field and takes over the responsibilities. That is why to increase the quality of education at this stage is the foremost mission of all the countries. By defining the term, quality is the level of satisfaction for which the consumer pays. In the case of education, the Consumer is the student as well as society. Therefore, quality education is the standard of education that satisfies the students and society both. The main objectives of this study were to identify the indicators of Total Quality Management (T.Q.M) in classroom to study the efforts of teachers to ensure TQM in classroom and to identify the ways to improve the quality of education at higher level. From the findings of the study it was revealed that the teachers did not covered the five standards of TQM elements completely, students were not completely satisfied by the teaching methodology during knowledge transitory process. Most of the teachers were not prepared before delivering there lectures, teacher showed biasness that discouraged the students. Teacher also ignored the daily assessment of the students, and use of the audio visual (AV) aids in classroom, obsolete teaching material, and ineffective material caused failure to produce total quality education, and failed to produce skilled work force. Based upon the conclusion of the study it is recommended that teacher may be punctual, teacher should use AV aids for teaching in classroom, teachers may be prepared well before delivering the lecture, teacher may encourage the classroom discussion, and teacher may treat equally in classroom.
Keywords: 330; Total quality management; classroom; higher education